Critique pour qui ? Politisation par l’enquête et objectivation de sa réception - Maud Simonet (Astérion)
This article seeks to offer a socially and politically situated analysis of the disenchantment produced by sociological research categorised as critical. It offers a step-by-step comparison of how a study on voluntary work (that produced disenchantment for some, truism for others) was received. It also gives weight to the fact that a research process can also lead to the politicisation of research. The article sheds light on two arguments for the autonomy of engagement that lies at the heart of the critique of a critique: one concerning the autonomy of the actors’ “citizen engagement” and of their relation to work, and the other concerning the autonomy of the researcher’s work and its “commitments”, generally presented as “research neutrality”. This reflexive attention to the effects of the research investigation not only on others but also on the author of the research ultimately questions the social and political scope of the “conception of hostile worlds” inscribed in the “doctrine of separated spheres” of work and commitment that, in the present case, concerns both the object and the practice of research.